Analisis Hermeneutik Dilthey pada Kisah Ashabul Kahfi dalam QS. Al-Kahfi: 9-26 - Anjani, Eka (STID Al-Hadid, 2023)
DILTHEY'S HERMENEUTIC ANALYSIS OF ASHABUL KAHFI STORY IN THE QURAN SURAH AL-KAHFI: 9-26. Hermeneutic study on Surah Al-Kahf: 9-26 needs to be carried out because there is another purpose that Allah wants to convey through this sura. God's purpose is known by using Dilthey's hermeneutic approach because this hermeneutic study emphasizes on objective meaning and social condition of the creator of the text. With an understanding of history, interpreter can empathize appear of the text and understand the intent of the text. based on this study, it is found that the meaning of QS. Al-Kahf 9-26 for the Prophet Muhammad and Muslims is a story to answer Quraysh questions and, at the same time, to show that Allah will grant the prayer of his pious servant. QS. Al-Kahf 9-26 also shows that migration does not always bring badness to Muslims. As for the Quraysh, QS. Al-Kahf is proof that Allah is the one and only god who deserves to be worshiped and shows the truth and power of Allah to resurrect humans on the Last Day. For the Jews, Al-Kahf will provide them correct information about the story and justify Muhammad's Prophethood by following muhammad.